A cultural response: the exploration of traditional dance and games as an HIV/AIDS intervention. A Zimbabwean case study - Ndlovu, Clayton Mboneli (My University, 2010)
ABSTRACT This study was a cultural response set to explore the use of indigenous knowledge found within the Zimbabwean traditional dances and games as an HIV/AIDS intervention. The focus of this creative led research was to analyze the process of exploring the use of traditional dances, games and songs as heuristic devices which also served as conceptual tools for framing the process of the study. Khaya African Arts composed of twelve members from Zimbabwe based in Johannesburg, South Africa, was the traditional dance group that participated in the process of the study. Khaya African Arts’ participation was appropriate for the study as the group has deep knowledge and performs traditional dances and games from Zimbabwe.